CLINICO-METABOLIC PECULІARITIES OF FLOW OF INTRAUTERINE VIRAL INFECTIONS IN NEWBORNS - A.S. Likhacheva; I.I. Redko; N.F. Efimenko; M.V. Pleten; L.M. Krichun (Bukovynian State Medical University, 2019)
The state of free-radical oxidation, antioxidant system and content of active metabolite of oxide nitrogen in newborns in acute period of intrauterine viral infections are investigated. Rise of lipid's free-radical oxidation, decrease antioxidant system and increase of metabolite of oxide nitrogen were ascertained. Mostly expressed metabolic disorders are in mix-viral TORCH-infections.